Cattle feeder perceptions of mandatory price reporting - Grunewald, S.; Ward, C.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Livestock price reporting mandated by the USDA was designed to increase available price data with the intent of providing producers with information to facilitate price discovery. Has the program been effective at accomplishing this goal? This study determined how cattle feeders, a primary target of the program, feel about mandatory price reporting effectiveness. This study reports results from a survey of cattle feeding companies located primarily in Kansas, Nebraska, Texas, and Iowa. Results indicate a diversity of opinions regarding the effectiveness of mandatory price reporting. On average, producers are neutral to slightly negative regarding the value of mandatory price reporting. Some of the dissatisfaction was associated with excessive or unrealistic expectations. Feedlot size, amount of custom feeding, and the percentage of cattle sold by the feedlot to its largest buyer had little systematic relationship to the manager’s perceptions regarding the usefulness of mandatory price reporting. In contrast, feedlot location and feedlot manager opinions about market structure were related to their opinions regarding mandatory price reporting.
Keywords: Beef; Mandatory price reporting